MONTELUKAST AND CETRIZINE MAY AMELIORATE PROGRESSION OF RHEUMATOID ARTHRITIS - Nimbalkar, Vikram V (International Journal of Clinical and Biomedical Research, 2016)
Rheumatoid arthritis is an autoimmune disorder. It is a chronic progressive disease resulting in inflammation of joints and painful deformity and immobility of various joints. Being an autoimmune disease, there’s lacuna in proper management of the disease. Current options like steroids and DMARD’S (disease modifying anti-rheumatic drugs) are the cornerstone in therapy of the disease, but have their own limitation. New drugs and better methods for management of rheumatoid arthritis are still evolving. The present review highlights the possible involvement of Montelukast, an antagonist of leukotriene receptors and Cetrizine, an antihistaminic drug in amelioration of the progression of the disease.